PENGARUH PRICE EARNINGS RATIO DAN KEBIJAKAN DIVIDEN TERHADAP RETURN SAHAM (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2013) - Anggraeni, Novitri; Sitanggang, J. P. (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2014)
This study aimed to examine the effect of the price earnings ratio and dividend policy on stock returns companies listed dibursa Indonesian effects period 2013. The population is companies listed Indonesian Stock Exchange securities. Data obtained from financial statements that have been published in 2013 and chose a sample of 39 companies. The analysis technique used is multiple linear regression and hypothesis testing using the partial-simultan-statistics and statistical confidence level of 21.1%. The results showed that the variable price earnings ratio and dividend policy have a significant effect on stock returns.